2012
DOI: 10.1016/j.bbabio.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Rhodobacter sphaeroides copper chaperones PCuAC and Sco (PrrC) in the assembly of the copper centers of the aa3-type and the cbb3-type cytochrome c oxidases

Abstract: The α proteobacter Rhodobacter sphaeroides accumulates two cytochrome c oxidases (CcO) in its cytoplasmic membrane during aerobic growth: a mitochondrial-like aa3-type CcO containing a di-copper CuA center and mono-copper CuB, plus a cbb3-type CcO that contains CuB but lacks CuA. Three copper chaperones are located in the periplasm of R. sphaeroides, PCuAC, PrrC (Sco) and Cox11. Cox11 is required to assemble CuB of the aa3-type but not the cbb3-type CcO. PrrC is homologous to mitochondrial Sco1; Sco proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 78 publications
(140 reference statements)
7
73
1
Order By: Relevance
“…Sco1 functioned in this assay as a disulfide reductase to maintain the correct oxidation state of the subunit II cysteine ligands. In vivo data with Rhodobacter sphaeroides confirmed that PCu A C and Sco1 co-participate in the assembly of a functional Cu A center in cytochrome aa 3 (24). Intriguingly, the authors of this study noticed a role of PCu A C also in the formation of the Cu B center of cytochrome cbb 3 .…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Sco1 functioned in this assay as a disulfide reductase to maintain the correct oxidation state of the subunit II cysteine ligands. In vivo data with Rhodobacter sphaeroides confirmed that PCu A C and Sco1 co-participate in the assembly of a functional Cu A center in cytochrome aa 3 (24). Intriguingly, the authors of this study noticed a role of PCu A C also in the formation of the Cu B center of cytochrome cbb 3 .…”
supporting
confidence: 60%
“…Two independent studies (Ref. 24 and this work) have now arrived at this new function. With an expedient combination of genetic and biochemical approaches, Thompson et al (24) have recently shown for R. sphaeroides that PCu A C works both for the metallation of the Cu A site of its aa 3 -type oxidase and for the metallation of the Cu B site of its cbb 3 -type oxidase.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The genes encoding two periplasmic copper chaperones, Sco1 and PCu A C, have been identified in the genome of T. thermophilus. PCu A C appears to deliver Cu ϩ into subunit II of the T. thermophilus cytochrome ba 3 respiratory oxygen reductase (1), and a role for the equivalent protein in Rhodobacter sphaeroides in the assembly of copper-containing respiratory oxidases has also been reported (60). Similarly, the Sco1/PrrC/SenC family of proteins has been implicated in copper acquisition by bacteria and in the assembly of copper-containing proteins, including respiratory oxygen reductases (11,23,24,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…PCu A C appears to deliver Cu ϩ into subunit II of the T. thermophilus cytochrome ba 3 respiratory oxygen reductase (1), and a role for the equivalent protein in Rhodobacter sphaeroides in the assembly of copper-containing respiratory oxidases has also been reported (60). Similarly, the Sco1/PrrC/SenC family of proteins has been implicated in copper acquisition by bacteria and in the assembly of copper-containing proteins, including respiratory oxygen reductases (11,23,24,59,60). Since P IB -type copper pumps have been implicated in the assembly of the copper-containing cbb 3 -type respiratory oxygen reductases (26,35), it is reasonable that the periplasmic copper chaperones present in T. thermophilus may function together with CopA and/or CopB in the assembly of the ba 3 -type and caa 3 -type copper-containing respiratory oxygen reductases present in T. thermophilus (55,61).…”
Section: Discussionmentioning
confidence: 99%